An Empirical Analysis of Determinants Influencing Whistleblowing Intention - Angela, Stefany Myrna; Noviyanti, Suzy; Purnamasari, Gisilowati (School of Accountancy, University of Agung Podomoro, 2025)
This study examines factors influencing the intention to whistleblowing among accounting students as prospective professional accountants. The analyzed factors include understanding professional accounting ethics, Machiavellian traits, and the perceived seriousness of fraud. The research employed a quantitative survey method, with a sample comprising undergraduate accounting students from the Faculty of Economics and Business at Satya Wacana Christian University from the 2021-2023 cohorts. Regression analysis results indicate that understanding professional accounting ethics positively influences whistleblowing intention, whereas Machiavellianism traits show no significant effect. Interestingly, the perceived seriousness of fraud negatively impacts whistleblowing intention, presumably due to fear of greater consequences if serious fraud is not reported. This study underscores the importance of robust professional ethics education and the establishment of a conducive and supportive organizational environment to encourage the courage to report misconduct within the accounting profession.